El perdón y el olvido en Centroamérica entre 1990-2000: una visión filosófica (aproximación a las políticas del perdón y el olvido) - Solano Villarreal, Diana (2008)
Throughout the 80’s of the last century in Central America, be- fell the worst crimes against humanity since the conquest. In order to end the massacres an ill-accomplished pact was formed, in which the silence of the victims has been the price. Today, two decades after the tragedy they continue trying to silence the desperate cry of a lashed people.